(untitled) (Research, Society and Development, 2021)
The flora of the Cerrado biome is made up of several fruit trees, which have a very impor-tant biotechnological potential. The application of these in the development of new products contributes to the appreciation of regional species. Among the characteristic plants of the region, the baru (Dipteryx alata Vog.), Of which the almond is widely used, stands out; ho-wever, the fiber-rich pulp is commonly discarded. Therefore, the objective of the present work was to develop noodles with substitutions of 10 and 20% of the wheat flour for the pulp flour of baru. Physicochemical, microbiological and sensorial analyzes were performed. The results showed that pasta with baru pulp flour can be classified as foods with high dietary fiber content and also had a lower carbohydrate content than the control sample (100% wheat flour). Sensory tests resulted in mean scores of 5 to 6 on a 9-point scale for noodles. Therefore, the presented results allow the expansion of the application of the pulp of baru in the food industry.